EFEKTIVITAS KOMUNIKASI ANTARPRIBADI PETANI DALAM BUDIDAYA PADI ORGANIK DI DESA GENTUNGAN KECAMATAN MOJOGEDANG KABUPATEN KARANGANYAR - Wijang Prasetiyo Aji; Suminah Suminah; Hanifah Ihsaniyati (Universitas Sebelas Maret, 2019)
This study aims to assess the factors that influence farmers' interpersonal communication in organic rice cultivation; assess the level of effectiveness of farmer interpersonal communication in organic rice cultivation; and analyze the influence of openness, empathy, attitudes and equality partially and simultaneously on the level of effectiveness of interpersonal communication of farmers in organic rice cultivation. The research location in Gentungan village, Mojogedang Subdistrict, Karanganyar Regency, with the consideration that Mojogedang Subdistrict has the highest organic rice production in Karanganyar Regency and Gentungan Village is the only village that has an organic rice certificate. This research was conducted using quantitative deskriptive method with census technique for all organic rice farmers who were certified with a total of 45 people. The data analysis used in this study is multiple linear regression. The results of the study indicate that; openness is included in the category of being quite open, empathy is included in the medium category, attitudes are included in the good category, and equality in the medium category; the level of effectiveness of interpersonal communication of farmers in organic rice cultivation is included in the high category; factors that influence interpersonal communication (openness, empathy, attitude and equality) simultaneously have a significant effect on the level of effectiveness of interpersonal communication while partially openness (X1), attitude (X3) and equality (X4) significantly influence the level of effectiveness interpersonal communication while empathy (X2) does not significantly influence the 95% confidence level.